2022
DOI: 10.3390/cancers14030528
|View full text |Cite
|
Sign up to set email alerts
|

The Obscure Potential of AHNAK2

Abstract: AHNAK2 is a protein discovered in 2004, with a strong association with oncogenesis in various epithelial cancers. It has a large 616 kDa tripartite structure and is thought to take part in the formation of large multi-protein complexes. High expression is found in clear cell renal carcinoma, pancreatic ductal adenocarcinoma, uveal melanoma, and lung adenocarcinoma, with a relation to poor prognosis. Little work has been done in exploring the function and relation AHNAK2 has with cancer, with early studies show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 84 publications
(167 reference statements)
1
12
0
1
Order By: Relevance
“…3 Additionally, AHNAK2, shown to promote UM cell proliferation and migration, 9 was found to correlate with infiltration of immune cell subpopulations such as CD8 + and CD4 + . 10 Our findings align with a recent report by Figueiredo et al, 5 which revealed that the downregulation of TLR1, a gene responsible for immune activation, is correlated with M3 status but not BAP1 expression, indicating epigenomic reprogramming independent of BAP1 mutations. These results highlight the importance of further exploring epigenetic regulation of the unique immune landscape of UM, which presents both challenges and opportunities for developing effective treatments for high-risk patients.…”
supporting
confidence: 92%
“…3 Additionally, AHNAK2, shown to promote UM cell proliferation and migration, 9 was found to correlate with infiltration of immune cell subpopulations such as CD8 + and CD4 + . 10 Our findings align with a recent report by Figueiredo et al, 5 which revealed that the downregulation of TLR1, a gene responsible for immune activation, is correlated with M3 status but not BAP1 expression, indicating epigenomic reprogramming independent of BAP1 mutations. These results highlight the importance of further exploring epigenetic regulation of the unique immune landscape of UM, which presents both challenges and opportunities for developing effective treatments for high-risk patients.…”
supporting
confidence: 92%
“…AHNAK nucleoprotein 2 (AHNAK2) is a member of the AHNAK protein family with a molecular weight greater than 600 kDa, 8 , 9 and its function has been gradually unveiled in recent years. Studies have reported that AHNAK2 is closely associated with oncogenesis in clear cell renal carcinoma, 10 thyroid carcinoma, 11 lung adenocarcinoma, 12 and uveal melanoma.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, a bioinformatic analysis indicated that AHNAK2 expression was positively correlated with CD4 + T cells, macrophages and neutrophils, although there was no careful experimental data or any rigorous hypothesis testing to back it up 15 . The latest review of AHNAKs has been delivered by Zardab et al, and provides a detailed summary of protein structure and oncology functions 16 …”
Section: Introductionmentioning
confidence: 99%
“…15 The latest review of AHNAKs has been delivered by Zardab et al, and provides a detailed summary of protein structure and oncology functions. 16 In this investigation, we detected the AHNAK2 expression levels in tumor and paired normal tissues and explored cancer databases from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) for gene expression and survival analysis. To verify our results from databases and explore the role of AHNAK2 in LUAD, we performed tumor cell phenotype assays, gene enrichment analysis and coimmunoprecipitation tests.…”
Section: Introductionmentioning
confidence: 99%